Sanctions against Russian oligarchs also affect their companies - Franziska Bremus; Pia Hüttl (DIW Weekly Report, 2022)
In February 2022, the EU Commission announced economic sanctions against Russian oligarchs. The goal was to exert pressure on the Kremlin: initially to stop deploying troops to the Donetsk and Luhansk regions and ultimately to end its attack on Ukraine. The present report investigates how these sanctions affect companies headed by Russian oligarchs. The empirical findings show that after sanctions are announced, the stock returns of companies with sanctioned oligarchs on their executive board were significantly lower than the stock returns of firms without sanctioned board members. This is due to, for example, signaling effects and legal and economic uncertainties. Investors may expect negative consequences for the companies with sanctioned oligarchs and therefore withdraw. Thus, personal sanctions can exert some economic pressure via the negative economic effects on firm value.
Keywords: G14; G34; P16; 330; sanctions; stock market reaction; event study; Ukraine; Russia; war